Effect of peroral anti-bacterial antiserum treatment on intestinal immune parameters of germ-free piglets intragastrically infected with virulent Salmonella typhimurium or enteropathogenic E. coli - Trebichavský, I; Dlabac, V; Reháková, Z (Veterinary immunology and immunopathology, 1999)
Germ-free piglets were orally infected with either enteropathogenic E. coli 055 or a virulent strain of Salmonella typhimurium. Orally applied antiserum against E. coli protected infected animals in spite of the fact that the bacteria were consistently found in mesenteric lymph nodes and other organs. By contrast, the application of an antiserum against S. typhimurium was without any effect on the outcome of infection. The treatment with anti-bacterial antiserum prevented inflammation of ileal mucosa (TNF-alpha and heat shock protein 65 expression) only in piglets infected with E. coli. A decrease in the frequency of ileal MAC320+ cells was observed in all infected piglets treated with antiserum.
Keywords: gnotobiologické modely; prasata; Administration, Oral; Swine; Fluorescent Antibody Technique; infekce vyvolané Escherichia coli; fluorescenční protilátková technika; Germ-Free Life; aplikace orální; Escherichia coli Infections; střevní sliznice; Escherichia coli; salmonelová infekce u zvířat; ileitida; Salmonella Infections, Animal; Animals; Ileitis; nemoci prasat; zvířata; Intestinal Mucosa; antisérum; Swine Diseases; Salmonella typhimurium; Immune Sera